Policy and Practice of Competency-Based Education in Indonesia: Challenges and Prospects for the Future - Idam Mustofa; Sokha Dara; Vann S Sok (Yayasan Adra Karima Hubbi, 2025)
Background. Competency-Based Education (CBE) has become a pivotal approach in reforming Indonesia's educational landscape to align with global standards and workforce demands. Despite its potential, the implementation of CBE in Indonesia faces numerous challenges ranging from policy inconsistencies to limited institutional readiness. Purpose. This study aims to analyze the current policy framework and practical applications of CBE in Indonesia, identifying key obstacles and exploring potential future directions. Method. Employing a qualitative research design, data were collected through document analysis and semi-structured interviews with policymakers, educators, and curriculum experts. Results. The findings reveal a gap between policy formulation and classroom practices, constrained by insufficient teacher training, inadequate assessment systems, and fragmented coordination among stakeholders. However, the study also highlights emerging opportunities, including increasing political will, technological integration, and regional initiatives to localize CBE models. Conclusion. The research concludes that while CBE in Indonesia remains at a developmental stage, its future prospects are promising, provided that strategic interventions are undertaken to address systemic barriers. Strengthening institutional capacity and fostering cross-sector collaboration are imperative to ensure the sustainability and effectiveness of CBE implementation.